(untitled) (Scientific journal of the Fergana State University, 2023)
In this article is given examples of the problems of the formation of children’s speech in a family environment, as well as research by scientists to study their communication. In particular, real-life events provide insight into children’s speech patterns, developmental processes, and various external and internal influences. In particular, the study of the child’s speech in the family, conducting various experiments, analyzing the problems associated with its socio-psychological characteristics have long been of interest to representatives of various fields, but, nevertheless, this direction has not yet been fully studied.